Influence of Extreme Long Endurance Sports Activity on Neopterin Excretion - Moser Berthold; Schroecksnadel Katharina; Hörtnagl Helmut; Rieder Josef; Fuchs Dietmar; Gottardis Marco (Pteridines, 2008)
Immune system activation has been observed during endurance exercise, but its relevance is largely unclear. We evaluated urinary neopterin excretion in an athlete competing in the Race Across America (RAAM), to determine whether neopterin excretion would indicate that immune system activation occurs during extreme endurance sport. Urinary samples were collected at the day before the race, during the whole RAAM, and, without a physical strain, seven days after the race. Neopterin normalized to creatinine concentration was determined by reversed-phase high-pressure liquid chromatography (HPLC). Data were analysed by repeated-measured analysis of variance (ANOVA). In the athlete, urinary neopterin concentration started to increase consistently after the start of the race until day four, followed by a decline thereafter, reaching values close to the starting value. The lowest average neopterin concentration was observed at day seven; this concentration was significantly lower than mean values at days 2- 6 (all p <0.05). Comparing the power output (Watt) with the neopterin concentrations at the same time point revealed a significant correlation (rs = 0.333; p <0.05). A comparison of average daily urinary neopterin excretion mean values between the test and control person showed significant differences at all time points, except for the specimen obtained at day seven. This pilot study supports the hypothesis that extreme long endurance strain at low intensities leads to an activation of the immune system. Neopterin levels could be a convenient tool to assess the immune system activation induced by training in athletes.